2016
DOI: 10.1073/pnas.1524616113
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-assisted mechanism of RNP disruption by the spliceosomal Brr2 RNA helicase

Abstract: The Brr2 RNA helicase disrupts the U4/U6 di-small nuclear RNAprotein complex (di-snRNP) during spliceosome activation via ATPdriven translocation on the U4 snRNA strand. However, it is unclear how bound proteins influence U4/U6 unwinding, which regions of the U4/U6 duplex the helicase actively unwinds, and whether U4/U6 components are released as individual molecules or as subcomplexes. Here, we set up a recombinant Brr2-mediated U4/U6 disnRNP disruption system, showing that sequential addition of the U4/U6 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 59 publications
1
24
0
1
Order By: Relevance
“…First, comparison of structures of full-length Brr2 in complex with the Prp8 Jab1 domain 55,56 with the structure of Brr2 bound to U4/U6 disnRNA in the framework of a yeast tri-snRNP 12 indicated that the plug domain of the NTR upon folding back onto the helicase cassettes competes with accommodation of stem I of the substrate, which Brr2 has to unwind during spliceosome activation. 29 In full agreement with this structural analysis, RNA binding studies showed that the NTR has no effect on singlestranded RNA binding by Brr2, but inhibits binding of substrates that additionally include a duplex resembling U4/U6 stem I. 56 Second, the NC-clamp connects the RecA-like and WH domains of the active NC and locks the RecA1 and the RecA2 domains in a conformation not conducive to ATP hydrolysis.…”
Section: Layer III -The Ntr As An Auto-inhibition Devicementioning
confidence: 58%
See 3 more Smart Citations
“…First, comparison of structures of full-length Brr2 in complex with the Prp8 Jab1 domain 55,56 with the structure of Brr2 bound to U4/U6 disnRNA in the framework of a yeast tri-snRNP 12 indicated that the plug domain of the NTR upon folding back onto the helicase cassettes competes with accommodation of stem I of the substrate, which Brr2 has to unwind during spliceosome activation. 29 In full agreement with this structural analysis, RNA binding studies showed that the NTR has no effect on singlestranded RNA binding by Brr2, but inhibits binding of substrates that additionally include a duplex resembling U4/U6 stem I. 56 Second, the NC-clamp connects the RecA-like and WH domains of the active NC and locks the RecA1 and the RecA2 domains in a conformation not conducive to ATP hydrolysis.…”
Section: Layer III -The Ntr As An Auto-inhibition Devicementioning
confidence: 58%
“…On the other hand, isolated Brr2 is a comparatively weak helicase, 25,40,41 and its U4/U6 di-snRNA substrate is stabilized by extensive base pairing and bound proteins, [12][13][14]29,42,43 suggesting that the helicase may also depend on specific activation to efficiently unwind the U4/U6 duplex at the right time.…”
Section: Brr2 Requires Tight Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has already been shown that deletion of U6 nt 1–54, which would prevent telestem formation, results in a decrease in Brr2 unwinding rate (46). More recently, it has been postulated that a competing structure in U6 actively participates in releasing of U4/U6 di-snRNP proteins and U4 unwinding in a model system (47). This competing structure may initially be the telestem, followed by the ISL.…”
Section: Discussionmentioning
confidence: 99%